Influence of Antimony Species on Electrical Properties of Sb-Doped Zinc Oxide Thin Films Prepared by Pulsed Laser Deposition - Sukittaya Jessadaluk; Narathon Khemasiri; Navaphun Kayunkid; Adirek Rangkasikorn; Supamas Wirunchit; Narin Tammarugwattana; Kitipong Mano; Chanunthorn Chananonnawathorn; Mati Horprathum; Annop Klamchuen; Sakon Rahong; Jiti Nukeaw (Nanomaterials, 2023)
content in the ablating target, leading to a qualitative change in energy per Sb ion, offers a new pathway to achieve high-performing optoelectronics using ZnO-based p-n junctions.
Keywords: ZnO doping and properties; Gas Sensing Nanomaterials and Sensors; Ga2O3 and related materials